2022
DOI: 10.3390/agronomy12010110
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic Effects of Selected Herbal Extracts on the Germination, Growth and Metabolism of Mustard and Oilseed Rape

Abstract: The use of plants that have high allelopathic potential as natural herbicides in the form of aqueous extracts is gaining popularity in environmentally friendly agriculture. Usually, their effect on the germination and growth of weeds is investigated. However, less attention is paid to the effect of the allelopathic compounds from extracts on cultivated plants. Therefore, the aim of this study was to evaluate the impact of herbal extracts that have allelopathic properties on selected physiological and biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 75 publications
2
12
0
Order By: Relevance
“…The lowest values were recorded for the 5% concentration of the peppermint oil (PN4) treatment, indicating that the higher the peppermint oil concentration in the emulsion, the more inhibitory effects on seed germination and seedling growth. To the best of our knowledge, our results are the first to show the changes in heat emission in the maize and barnyard grass seedlings treated with the PNs but are consistent with those of [ 43 , 44 , 47 ], who found that bioactive compounds from allelopathic plants quantitatively and qualitatively change the heat emission patterns of the acceptor seedlings.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The lowest values were recorded for the 5% concentration of the peppermint oil (PN4) treatment, indicating that the higher the peppermint oil concentration in the emulsion, the more inhibitory effects on seed germination and seedling growth. To the best of our knowledge, our results are the first to show the changes in heat emission in the maize and barnyard grass seedlings treated with the PNs but are consistent with those of [ 43 , 44 , 47 ], who found that bioactive compounds from allelopathic plants quantitatively and qualitatively change the heat emission patterns of the acceptor seedlings.…”
Section: Discussionsupporting
confidence: 89%
“…The obtained spectra showed that the peppermint oil in each of the PNs concentrations accelerated the breakdown of polysaccharides into monosaccharides in the initial seed germination stage as their increase was observed. This may point to the decomposition of storage materials, which is concurrent with the effects observed in other works, e.g., of essential hemp oil on wild oat and cornflower seedlings [ 54 ], and herbal extracts from arnica, ribwort, hypericum, milfoil, sunflower, and sage on seedlings of mustard and oilseed rape [ 47 ]. Additionally, a hierarchical analysis of similarity proved significant differences in the chemical composition of seedlings treated with nanoemulsions with peppermint oil (first group) versus control and surfactants treated plants (second group).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Considering that a large number of diverse methods used to determine the phytotoxic effects of EOs and PEs concerning plants [ 61 , 62 ] rather complicate the overall picture, it was decided to determine the phytotoxic concentrations for each of the substances planned for use in vivo in relation to soybean. Moreover, there are precedents for the use of EOs as contact herbicides for weed control, in which a decrease in crop yield was observed [ 63 , 64 ]. In the current study, all tested substances were phytotoxic to soybean seeds and leaves at certain concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…A complementary method that allows determining the effect of O 3 on photosynthesis is gas exchange analysis, i.e., net photosynthesis, as well as transpiration, stomatal conductance and intracellular CO 2 concentration [6,13,24]. In turn, FT-Raman spectroscopy and light reflectance analysis allow to assess the chemical compositions of plants-in particular, the estimation of the total protective pigments content (such as anthocyanins, flavonols and carotenoids) without affecting the tissue structure [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%